Limited distal duodenal resection: Surgical approach and outcomes. A case series() - Golhar, Ankush (Ann Med Surg (Lond), 2018)
INTRODUCTION: Tumours involving the duodenum are usually treated with pancreaticoduodenectomy, which may be associated with considerable morbidity. Limited distal duodenal resection, a relatively smaller procedure, can be done in some of these patients. We describe our experience with this operation for such lesions. METHODS: We retrospectively analyzed, from prospectively collected data 10 consecutive patients who underwent limited duodenal and proximal jejunal resection between March 2011 and Nov 2015. RESULTS: There were 8 males and 2 females who had a median age of 47 years. Their common presentations were abdominal pain (50%) and upper gastrointestinal bleeding (40%). Five had malignancy (adenocarcinoma: 2, neuroendocrine tumours: 2, non Hodgkin's lymphoma 1). Three had gastrointestinal stromal tumours (GISTs) and 2 had other benign tumours (lipoma 1, ectopic pancreas 1). The 30-day post-operative morbidity rate was 60% (n = 6) with mostly minor complications (Clavien grade 1 or 2). Median post-operative stay was 9 (range, 6–13) days. All ten patients were alive without recurrence after a median follow up of 26.5 months. CONCLUSION: Limited distal duodenal resection is a feasible surgical alternative to a pancreaticoduodenectomy in carefully selected patients with benign and some malignant tumours of the third and fourth part of the duodenum.